REPRESENTATION OF MYTHOLOGICAL CHARACTERS THROUGH NUMBERS IN ENGLISH AND UZBEK FAIRY TALES - Khantemirova Kamola Erkinovna (Galaxy International Interdisciplinary Research Journal, 2023)
This article discusses the representation of mythological characters in English and Uzbek fairy tales, as well as certain mythological aspects of numbers in fairy tales with the participation of these mythological characters.